2021
DOI: 10.1111/gwao.12752
|View full text |Cite
|
Sign up to set email alerts
|

Ties that bind: An inclusive feminist approach to subvert gendered “othering” in times of crisis

Abstract: The COVID-19 pandemic, as an ongoing societal crisis, compounds pre-existing intersectional inequalities. Since the start of this crisis, those on the margins-women, single parents, LGBTQ+, Black, Asian, and Minority Ethnic peoplesand those living in precarity and poverty found themselves increasingly "othered. " As a group of academics who encounter gendered reality in disparate ways, we unite through this paper to prioritize a collective ethic of care as a counter-narrative to the "business as usual" rhetori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It is apparent that the documentary emphasises and upholds a rigid ideological reasoning that assumes cisnormativity; an assumption and expectation that all people are and should be, by default, cisgender (Sumerau et al, 2016), which obviously privileges cisgender individuals' experiences while disadvantaging others whose gender identity does not fit the binary. Instead of shedding light on the media's symbolic annihilation of the trans community (Abdellatif et al, 2021), the silencing, discrimination, harassment and violence that transgender and gender nonconforming people experience (see Schilt and Lagos, 2017), or offering a safe inclusionary space for the trans community for their stories to be told, voices to heard and included, the documentary explicitly states that transgender and gender nonconforming individuals should be denied access to existence, let alone defining their own reality or choosing their own pronouns. Such flawed ideological assumptions and toxic logic that seeks to devalue 'othered' bodies' experiences and erase trans and nonconforming people's basic human right to live is harmful to the experiences of sexual and gender minorities within organisations and have implications on organisational equity, diversity and inclusion policies.…”
Section: Amal Abdellatifmentioning
confidence: 99%
“…It is apparent that the documentary emphasises and upholds a rigid ideological reasoning that assumes cisnormativity; an assumption and expectation that all people are and should be, by default, cisgender (Sumerau et al, 2016), which obviously privileges cisgender individuals' experiences while disadvantaging others whose gender identity does not fit the binary. Instead of shedding light on the media's symbolic annihilation of the trans community (Abdellatif et al, 2021), the silencing, discrimination, harassment and violence that transgender and gender nonconforming people experience (see Schilt and Lagos, 2017), or offering a safe inclusionary space for the trans community for their stories to be told, voices to heard and included, the documentary explicitly states that transgender and gender nonconforming individuals should be denied access to existence, let alone defining their own reality or choosing their own pronouns. Such flawed ideological assumptions and toxic logic that seeks to devalue 'othered' bodies' experiences and erase trans and nonconforming people's basic human right to live is harmful to the experiences of sexual and gender minorities within organisations and have implications on organisational equity, diversity and inclusion policies.…”
Section: Amal Abdellatifmentioning
confidence: 99%
“…Our use of the term “othering” reflects that of the OS literature on gender, as exemplified in the work of Özbilgin and Woodward (2004), and more recently Mandalaki (2021) and Abdellatif et al. (2021), to name a few.…”
Section: Analysis and Identified Themesmentioning
confidence: 99%
“…As a result, both men and women are understood as "other" rather than equal partners within the infertile or nonreproductive couple. Our use of the term "othering" reflects that of the OS literature on gender, as exemplified in the work of Özbilgin and Woodward (2004), and more recently Mandalaki (2021) and Abdellatif et al (2021), to name a few.…”
Section: Male Infertility As An Othering Experiencementioning
confidence: 99%
“…Overall, prior research has often construed workplaces as challenging environments for LGBTQ employees, as these places require additional efforts for managing the various tensions, silences, and fears embedded in a heteronormative culture. Furthermore, it has been shown that sexualities that do not conform to the dominant norm are pushed to the margins in workplaces (Abdellatif et al., 2021; Ng & Rumens, 2017; Rumens, 2016; Sue, 2010) and, thus, daily life and employee experience of gay individuals still require further theorization.…”
Section: Introductionmentioning
confidence: 99%
“…LGBTQ employees, as these places require additional efforts for managing the various tensions, silences, and fears embedded in a heteronormative culture. Furthermore, it has been shown that sexualities that do not conform to the dominant norm are pushed to the margins in workplaces (Abdellatif et al, 2021;Ng & Rumens, 2017;Rumens, 2016;Sue, 2010) and, thus, daily life and employee experience of gay individuals still require further theorization. This discussion is informed by conceptual frameworks developed in diversity and gender studies, as well as critical organization studies.…”
Section: Introductionmentioning
confidence: 99%